Evidence Summary of Temperature Management for Comatose Patients after Cardiopulmonary Resuscitation in ICUs - Zhuo Yang; Ting Ni; Yan Yang; Hui Zhang; Hongli Chi (Applied Bionics and Biomechanics, 2022)
Objective. This study aims to select and summarize the best evidence of temperature management for comatose patients after cardiopulmonary resuscitation in intensive care units (ICUs) at home and abroad. Method. Some well-known databases at home and abroad have been searched to find the guidelines, expert consensus, original documents, evidence summaries, and systematic evaluation about temperature management for comatose patients after cardiopulmonary resuscitation in ICUs. The databases included PubMed, Up to Date, Cochrane Library, the website of Registered Nurses’ Association of Ontario, the Guideline Library of National Institute for Health and Clinical Excellence of the UK, China National Knowledge Infrastructure (CNKI), Wanfang Database, and VIP. The period for search is from the establishment of each database to the present. Two researchers who have received evidence-based nursing training and passed the examination evaluated, extracted, and integrated the literature quality with a blind method to summarize the best evidence. Results. A total of 10 pieces of literature were included in this study, including 4 in Chinese and 6 in English. Specifically, there were 4 guidelines, 1 expert consensus, 2 evidence summaries, 1 systematic evaluation, 1 literature review, and 1 comparative experiment, accounting for 40.0%, 10.0%, 20.0%, 10.0%, 10.0%, and 10.0%, respectively. The literature and materials were all qualified, and there was no heterogeneity and no significant publication bias in the included literature. The best evidence involved mild hypothermia therapy, rewarming, prevention of mild hypothermia-related complications, and nutritional support, with a total of 21 pieces of evidence (including 11, 3, 5, and 2 pieces of evidence, respectively). In terms of the recommendation grade, 7 pieces of evidence were at Grade A and 14 at Grade B. Conclusion. Health care providers should implement hypothermia management in comatose patients after cardiopulmonary resuscitation in ICUs, pay attention to the prevention of related complications, and provide enteral nutrition support.